2018
DOI: 10.1002/ejic.201701293
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Carbon Dioxide to the Lewis Acid Site of a Zinc‐Substituted Polyoxometalate and Formation of an Adduct Using a Polyoxometalate–2,4,6‐Trimethylpyridine Frustrated Lewis Pair

Abstract: The coordination of CO 2 to Lewis bases is wellknown; however, its binding to Lewis acids is much less common. The ligation of CO 2 to a zinc-substituted Wells-Dawson type polyoxometalate yielded [(n-C 8 H 17 ) 4 N] 8 [α 2 -P 2 W 17 O 61 Zn-(CO 2 )], which was studied by variable temperature 1 H NMR, 13 C NMR, and 31 P NMR spectroscopy from room temperature to [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Following optimization [260], allowing the reaction to be conducted in dimethylformamide and not in neat isocyanate, more than 60 different Pt(IV) species were thus prepared, arousing interest as possible anticancer agents (see Reaction of an amine with a metal carboxyl complex (Scheme 18e). Another type of synthesis comprises the reactions of amines (or N-donors in general) with a metal carboxyl complex, i.e., bicarbonate [269], formate [270,271], carbonate ester [272] or a CO2 adduct directly [273]. As an example, the intramolecular attack of an amine group belonging to a tetradentate pyridylamine ligand onto a Zn(II)-HCO3 species resulted in carbamate generation [269] (Scheme 26a).…”
Section: Heteroleptic Carbamato Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following optimization [260], allowing the reaction to be conducted in dimethylformamide and not in neat isocyanate, more than 60 different Pt(IV) species were thus prepared, arousing interest as possible anticancer agents (see Reaction of an amine with a metal carboxyl complex (Scheme 18e). Another type of synthesis comprises the reactions of amines (or N-donors in general) with a metal carboxyl complex, i.e., bicarbonate [269], formate [270,271], carbonate ester [272] or a CO2 adduct directly [273]. As an example, the intramolecular attack of an amine group belonging to a tetradentate pyridylamine ligand onto a Zn(II)-HCO3 species resulted in carbamate generation [269] (Scheme 26a).…”
Section: Heteroleptic Carbamato Complexesmentioning
confidence: 99%
“…Reaction of an amine with a metal carboxyl complex ( Scheme 18 e). Another type of synthesis comprises the reactions of amines (or N -donors in general) with a metal carboxyl complex, i.e., bicarbonate [ 269 ], formate [ 270 , 271 ], carbonate ester [ 272 ] or a CO 2 adduct directly [ 273 ]. As an example, the intramolecular attack of an amine group belonging to a tetradentate pyridylamine ligand onto a Zn(II)-HCO 3 species resulted in carbamate generation [ 269 ] ( Scheme 26 a).…”
Section: Synthesis Structure and Reactivity Of Metal Carbamatesmentioning
confidence: 99%
“…As early as 1988, Kozik and co-workers first reported the coordination of CO 2 with several POM derivatives [16]. Afterwards more researches about the interaction of POMs with CO 2 emerged [17,18,19,20,21,22]. Since the interaction between CO 2 and POM is one of the crucial steps for catalytic transformations of CO 2 , it is necessary to clarify the mode of such interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Hill et al reported the sandwich-type encapsulation of CO32 via forming [(YOH 2 ) 3 (CO 3 )( A -α-PW 9 O 34 ) 2 ] 11− [20]. [SiMo 11 CoO 38 (CO 2 )] n polymeric chains reported by Xu et al displayed the μ-η 1 ,η 1 -OCO linear coordination mode of POM-CO 2 interaction [21]. Two kinds of POM-CO 2 interaction modes were observed on [( n -C 8 H 17 ) 4 N] 8 [α 2 -P 2 W 17 O 61 Zn-(CO 2 )] [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation